PENGARUH PERMAINAN TRADISIONAL PETAK UMPET TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK DI KELOMPOK B TK SAMPOROA DWP KOTA PALU - Dwiyanti, Ulfa; Agusniati, Andi; ., Amrullah (Bomba: Jurnal Pembangunan Daerah, 2023)
Abstract This article examines the social emotional problem of children who have not developed according to expectations. In an effort to resolve this problem, research was carried out to determine the effect of implementing the traditional game of hide and seek on the social emotional development of children in group B of the Samporoa Kindergarten DWP, Palu City. The method used is quantitative and experimental research type. The subjects were 12 children consisting of 5 boys and 7 girls enrolled in the 2022/2023 school year. Data collection techniques include observation, interviews and documentation, then the data is analyzed quantitatively. Observation results before treatment on the interaction aspect were (0%) in the BSB category, (25%) in the BSH category, (42%) in the MB category and (33%) in the BB category. Responsible aspects (0%) in the BSB category, (8%) in the BSH category, (67%) in the MB category and (25%) in the BB category. Aspects of protecting the environment (0%) in the BSB category, (8%) in the BSH category, (42%) in the MB category and (50%) in the BB category. The results of observations after being given treatment in the interaction aspect were (33%) in the BSB category, (42%) in the BSH category, (50%) in the MB category and (0%) in the BB category. Responsible aspects (17%) in the BSB category, (25%) in the BSH category, (50%) in the MB category and (8%) in the BB category. Aspects of protecting the environment (8%) in the BSB category, (25%) in the BSH category, (50%) in the MB category and (17%) in the BB category. If we look at the t value, it can be explained that the calculated t is -6.268 with a significance level of 0.000. Because the significance is <0.05, it can be concluded that ho is rejected and h1 is accepted, meaning that there is an influence of the application of the traditional game of hide and seek on the social emotional development of children in group B of the Samporoa DWP Kindergarten, Palu City. Keywords: Traditional game of hide and seek, social emotional development Abstrak Artikel ini mengkaji tentang masalah sosial emosional anak belum berkembang sesuai harapan upaya menyelesaikan masalah tersebut dilakukan penelitian untuk mengetahui pengaruh penerapan permainan tradisional petak umpet terhadap perkembangan sosial emosional anak di kelompok B TK Samporoa DWP Kota Palu. Metode yang digunakan adalah kuantitatif dan jenis penelitian eksperimen. Subyek berjumlah 12 anak yang terdiri dari 5 anak laki-laki dan 7 anak perempuan terdaftar pada tahun ajaran 2022/2023. Teknik pengumpulan data dengan cara observasi, wawancara dan dokumentasi, selanjutnya data dianalisis secara kuantitatif. Hasil pengamatan sebelum diberikan perlakuan pada aspek berinteraksi (0%) dalam kategori BSB, (25%) kategori BSH, (42%) kategori MB dan (33%) kategori BB. Aspek bertanggung jawab (0%) dalam kategori BSB, (8%) kategori BSH, (67%) kategori MB dan (25%) kategori BB. Aspek menjaga lingkungan (0%) dalam kategori BSB, (8%) kategori BSH, (42%) kategori MB dan (50%) kategori BB. Hasil pengamatan sesudah diberikan perlakuan pada aspek berinteraksi (33%) dalam kategori BSB, (42%) kategori BSH, (50%) kategori MB dan (0%) kategori BB. Aspek bertanggung jawab (17%) dalam kategori BSB, (25%) kategori BSH, (50%) kategori MB dan (8%) kategori BB. Aspek menjaga lingkungan (8%) dalam kategori BSB, (25%) kategori BSH, (50%) kategori MB dan (17%) kategori BB. Jika dilihat dari nilai t dapat dijelaskan bahwa t hitung sebesar -6.268 dengan taraf signifikan 0,000. Karena signifikasi <0,05 maka dapat disimpulkan bahwa ho ditolak dan h1 diterima, berarti terdapat pengaruh penerapan permainan tradisional petak umpet terhadap perkembangan sosial emosional anak di kelompok B TK Samporoa DWP Kota Palu. Kata Kunci: Permainan tradisional petak umpet, perkembangan sosial emosional